MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN DENGAN MENGGUNAKAN STRATEGI MULTIPLE GAMES PADA SISWA KELAS II SDN 56 BUTON - Yurfiah, Yurfiah (TAKSONOMI: Jurnal Penelitian Pendidikan Dasar, 2021)
The purpose of this study was to describe the ability to read at the beginning can be improved by using multiple games strategy. The benefits of this research are increasing student participation, improving the quality of learning for teachers and for schools to improve student learning outcomes. This research is a Classroom Action Research (CAR) which recycles / cycles includes planning, implementing actions, observing and reflecting. This research was conducted in class II SDN 56 Buton. The subjects of this research proposal were 19 grade II students who were registered and active in the 2020/2021 school year. The results of this study were conducted in 2 cycles, and each cycle consisted of 2 learning meetings, and each cycle an observation test was carried out. Action, cycle 1, and cycle 2. The increase can be seen from the results of the average score of the students' initial ability of 29.21 after being given action in cycle 1 shows an increase in the average value of student subjects by 59.74 and cycle 2 increases the average value. an average of 84.21. The results of the second cycle of action showed that the results of the achievement of the subject's score showed that the results of the achievement of the subject's score increased and could far exceed the predetermined minimum completeness criteria (KKM) value of 65 so that the action was stopped.